The Effect of Liquidity and Solvency on PT. Sharia Banking is Listed on the Indonesia Stock Exchange - Burhanuddin; Suwedy (Universitas Muhammadiyah Palu, 2023)
Ratio Financing to Deposit Ratio (FDR) and Capital Adequacy Ratio (CAR) on the share price of PT. Islamic Banking in 2017-2019. This study uses secondary data obtained from PT's annual published financial statements. Islamic Banking for the Year 2017-20019 is available on the related Bank's website. The data analysis technique used in this research is multiple linear regression analysis. The analytical tool used in this research is the Statistical Package For the Social Sciences (SPSS) version 16.0. The results of this study indicate that the Financing to Deposit Ratio and the Capital Adequate Ratio partially or simultaneously have no significant effect on share prices.